Variation in the perception of desired qualities of police officers among trainees and senior police officers. Insights into the process and efficacy of police training. Issue 3 (3rd July 2019) - Kumar, T. K. Vinod
ABSTRACT: Police training is the process of imparting knowledge, skills, and values to police personnel. The study analyses a survey data on the perception of trainees and senior experienced officers regarding desired professional qualities in police officers. There is a high degree of congruence, in the assessment of values which are important for police, among the two groups. There are also differences among the two groups regarding the evaluation of the importance of interpersonal skills and human qualities. The study attempts to explain the similarities and the differences in perception by examining the conservative and innovative nature of police training, and the role of experience in developing an appreciation of human qualities. The study underlines the importance of police training as a mechanism to maintain the stability of operations in the organisation and its pivotal role in bringing about change in the police.